Magnitude of phonetic distinction predicts success at early word learning in native and non-native accents - Escudero, Paola; Best, Catherine T.; Kitamura, Christine; Mulak, Karen E. (Frontiers in Psychology, 2014)
Although infants perceptually attune to native vowels and consonants well before 12 months, at 13–15 months, they have difficulty learning to associate novel words that differ by their initial consonant (e.g., BIN and DIN) to their visual referents. However, this difficulty may not apply to all minimal-pair novel words. While Canadian English (CE) 15-month-olds failed to respond to a switch from the newly learned word DEET to the novel nonword DOOT, they did notice a switch from DEET to DIT (Curtin, Fennell, & Escudero, 2009). Those authors argued that early word learners capitalize on large phonetic differences, seen in CE DEET–DIT, but not on smaller phonetic differences, as in CE DEET–DOOT. To assess this hypothesis, we tested Australian English (AusE) 15-month-olds, as AusE has a smaller magnitude of phonetic difference in both novel word pairs. Two groups of infants were trained on the novel word DEET and tested on the vowel switches in DIT and DOOT, produced by an AusE female speaker or the same CE female speaker as in Curtin et al. (2009). If the size of the phonetic distinction plays a more central role than native accent experience in early word learning, AusE children should more easily recognize both of the unfamiliar but larger CE vowel switches than the more familiar but smaller AusE ones. The results support our phonetic-magnitude hypothesis: AusE children taught and tested with the CE-accented novel words looked longer to both of the switch test trials (DIT, DOOT) than same test trials (DEET), while those who heard the AusE-accented tokens did not notice either switch. Implications of our findings for models of early word learning are discussed.